Hematology Reference Values in Indonesian Children - Ina S. Timan; Aryati Aryati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2023)
Every clinical laboratory has to establish its reference ranges for every parameter analyzed. These reference values are intervals considered normal in a healthy person's physiological condition. It will be used by the clinician or other health professionals to interpret the laboratory test results of the patient for making diagnostic decisions, monitoring patient therapy, and predicting the prognosis and it is also used in epidemiology studies. A reference range is defined as an interval in which 95% of a reference population’s values fall. It is very crucial to establish reference intervals for the local population as it is sometimes affected by ethnicity, nutrition, food habits, and  economic and other local conditions. Hematology is the most common test performed in a clinical laboratory, and the most used parameter by the clinician including pediatricians. There up to now no well-established reference interval for hematological parameters in pediatrics and children in Indonesia. The reference interval used for hematology parameters in Indonesia is based on reference intervals from other countries or the manufacturer of the hematology analyzers used in a particular laboratory. Establishing a population-specific hematology reference interval is very difficult for pediatrics and children, so it is rarely performed. This study aims to compile the results of hematology parameters from Indonesian children to establish an Indonesian reference value for hematology. The method used was compiling data for the hematology parameter intervals based on studies performed in the Indonesian population and presented as 95% confidence intervals. A pediatric reference range for several hematology parameters has been established based on 3 groups of age in Indonesian children.